Departures : the Abbey Theatre on international stages 1975-2005 - Coen, Lisa (Trinity College (Dublin, Ireland). School of English, 2012)
This thesis and the included production history of Abbey Theatre tours form part of a broader project under the aegis of the Irish Theatrical Diaspora, The Internationalisation of Irish Drama, 1975-2005. This project includes Shelley Troupe's research and production history of Druid Theatre Company, Galway from 1975-2005 and her Ph.D. thesis Theatre and Space: Druid's Productions of Tom Murphy's Plays, 1984-1987.
Keywords: English, Ph.D.; Ph.D. Trinity College Dublin.